Proceedings of the 2016 CHI Conference Extended Abstracts on Human Factors in Computing Systems 2016
DOI: 10.1145/2851581.2892281
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Impact of Avatar Color on Game Experience in Educational Games

Abstract: The color red has been shown to hinder performance, motivation, and affect in a variety of contexts involving cognitively demanding tasks [16, 47, 49, 22, 11, 32, 44, 64, 41]. Teams wearing red have been shown to impair the performance of opposing teams [7, 28, 57, 21], present even in online gaming [27]. Although color is strongly contextual (e.g., red-failure association), its effects are posited to be subconscious [15] and operate powerfully even on nonhuman primates, e.g., Rhesus macaques (Macaca mulatta) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
2

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…Levels 10-12 require using all preceding commands in addition to conditionals (See Figures 1 and 2). Mazzy has been used previously as an experimental testbed for evaluating the impacts of avatar type on performance and engagement in an educational game (Kao and Harrell 2015b, 2015c, 2015d, 2016a, 2016b, 2016c, 2017Kao, 2018).…”
Section: Mazzy: a Cs Programming Gamementioning
confidence: 99%
“…Levels 10-12 require using all preceding commands in addition to conditionals (See Figures 1 and 2). Mazzy has been used previously as an experimental testbed for evaluating the impacts of avatar type on performance and engagement in an educational game (Kao and Harrell 2015b, 2015c, 2015d, 2016a, 2016b, 2016c, 2017Kao, 2018).…”
Section: Mazzy: a Cs Programming Gamementioning
confidence: 99%
“…HCI and games researchers have long been interested in games and learning [40-42, 48, 50, 56, 60, 62, 103, 118, 120]. This includes studies on tutorials [3], differences in frequent versus infrequent gamers' reactions to tutorials [82], leveraging reward systems [32], encouraging a growth mindset, or the idea that intelligence is malleable [55,86,87], avatars [57,59,63,66], embellishment [58,65], and many more. AI and games researchers have also begun to take interest, such as the automatic generation of video game tutorials [36,37], and the adaptation of tutorials to individual user skill levels [8].…”
Section: Related Workmentioning
confidence: 99%
“…Studies have shown that the color of the avatars takes a very important role when it comes to the player's identification with the characters [Kao and Harrell, 2016]. Aiming to avoid reinforcing stereotypes and, mainly, to make it easier for the player to identify with the story and the characters displayed, all of them were drawn in a shade of blue, as shown in Figure 1.…”
Section: Magnetmentioning
confidence: 99%